Vela Pećina cave near Kali on Ugljan – a new late upper Paleolithic site in the northern Dalmatian islands (Archaeologia Adriatica, 2025)
The paper presents the results of trial excavations at Vela Pećina cave near Kali on the island of Ugljan, and in particular the results of techno-typological and petrographic analyses of the lithic find assemblage. It considers the site’s significance in the settlement grid of Upper Palaeolithic hunter-gatherers within the context of the time period confirmed by radiocarbon dating and the site’s geographic location on the margins of the presently submerged Adriatic Plain.
Keywords: Vela Pećina; Ugljan; Upper Palaeolithic; Epigravettian; lithics